Antimicrobial resistance in the Pacific Island countries and territories. Issue 4 (28th April 2020) - Loftus, Michael; Stewardson, Andrew; Naidu, Ravi; Coghlan, Ben; Jenney, Adam; Kepas, Jonila; Lavu, Evelyn; Munamua, Alex; Peel, Trisha; Sahai, Vinita; Tekoaua, Rosemary; Tudravu, Litia; et al.
Abstract : Antimicrobial resistance (AMR) is a critical global health threat with a disproportionate impact on low-income and middle-income countries (LMICs) due to their higher burden of infections, reduced laboratory surveillance infrastructure and fewer regulations governing antimicrobial use among humans or animals. While there have been increasing descriptions of AMR within many LMICs in WHO's Western Pacific and South East Asian regions, there remains a paucity of data from Pacific Island countries and territories (PICTs). The PICTs represent 22 predominantly middle-income countries and territories with a combined population of 12 million people and 20 official languages, spread over hundreds of separate islands spanning an area corresponding to more than 15% of the earth's surface. Our paper outlines the present state of the evidence regarding AMR in PICTs—discussing the present estimates of AMR and their accompanying limitations, important drivers of AMR, as well as outlining key priorities and potential solutions for tackling AMR in this region. Significant areas for action include developing National Action Plans, strengthening laboratory surveillance systems and educational activities targeted at both healthcare workers and the wider community. Ensuring adequate funding for AMR activities in PICTs is challenging given competing health and environmental priorities, in this context global or regional funding initiatives such as the Fleming Fund can play a key role.